The Choice of Agreement Over Acquiescence for Achieving Equity in the Maritime Delimitation Between Somalia and Kenya in indian ocean - Daddy , Malangu Mposhy Kasambule (Revue Internationale du Chercheur, 2025)
Abstract: The facts revealed in the Somalia/Kenya case have brought back to the forefront of delimitation law the issue of acquiescence in supporting a claim to a maritime territorial title. In its argument, Kenya encountered real difficulty in its claim, and the effort it undertook did not advance the debate in any way. The Court therefore remained unwavering regarding the “path of agreement”, confirming that it remains the condition for establishing an explicit commitment of a State’s will to be bound concerning the transfer of territorial rights over a maritime area. This, moreover, reaffirms the strict nature of the conditions for applying “tacit agreement”, whose clarity so far calls for no redefinition.